2007
DOI: 10.1007/s10616-007-9050-y
|View full text |Cite
|
Sign up to set email alerts
|

Targeted genetic modification of cell lines for recombinant protein production

Abstract: Considerable increases in productivity have been achieved in biopharmaceutical production processes over the last two decades. Much of this has been a result of improvements in media formulation and process development. Though advances have been made in cell line development, there remains considerable opportunity for improvement in this area. The wealth of transcriptional and proteomic data being generated currently hold the promise of specific molecular interventions to improve the performance of production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 54 publications
(50 reference statements)
0
3
0
3
Order By: Relevance
“…These barrier elements include scaffold or matrix attachment regions (S/MARs), insulators, anti‐repressor elements, and ubiquitous chromatin opening elements (UCOEs) (Barnes and Dickson, 2006; Kwaks and Otte, 2006). Alternative approaches to improving productive and stable transgene expression rely on the targeting of highly transcribed sites within the host cell genome by means of heterologous site‐specific recombination (Barron et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…These barrier elements include scaffold or matrix attachment regions (S/MARs), insulators, anti‐repressor elements, and ubiquitous chromatin opening elements (UCOEs) (Barnes and Dickson, 2006; Kwaks and Otte, 2006). Alternative approaches to improving productive and stable transgene expression rely on the targeting of highly transcribed sites within the host cell genome by means of heterologous site‐specific recombination (Barron et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Sandström et al demonstrated the ability to bind nucleic acids onto gold nanoparticles [151], and a similar modification has been done by Rosi et al where tetrathiol-modified antisense oligonucleotides were bound to 13-nm gold nanoparticles [152]. Being able to conjugate nucleic acids to nanoparticles opens up the possibility of targeted gene delivery, which could, for example, lead to genes coding for a specific protein to be delivered to a cell that was either deficient in that protein or could not produce the protein themselves [156]. It has also been exhibited that gold nanoparticles modified with DNA can transfect cancer cells [157] (Table 4).…”
Section: Bio-medical Applications Of Metal Nanoparticlesmentioning
confidence: 99%
“…Esto puede tener como consecuencia la interrupción de genes importantes en el genoma del hospedero y dar origen a genotipos desconocidos que son incapaces de sintetizar la PR. En el mejor de los casos se puede producir la PR, pero con bajo rendimiento (Barron et al, 2007).…”
Section: Limitaciones En La Producción De Prunclassified
“…Estos errores aleatorios son difíciles de detectar, ya que producen una mezcla heterogénea de polipéptidos. Las proteínas alteradas pueden estar presentes en cantidades muy pequeñas, pero el número total de moléculas defectuosas podría ser sustancial en el rendimiento de la PR (Barron et al, 2007;Mattanovich et al, 2004).…”
Section: Limitaciones En La Producción De Prunclassified
See 1 more Smart Citation